2009
DOI: 10.1111/j.1749-6632.2009.04982.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Mood in the Perimenopause

Abstract: The focus of this chapter is the relationship between the onset of depression in women and the reproductive events of the menopause transition. Epidemiologic studies have documented that the majority of women do not become depressed during the menopause transition. However, recent longitudinal studies suggest that in some women, the reproductive events related to the menopause transition could play a role in the onset of depression. No abnormality of ovarian hormones has been identified that distinguishes wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 178 publications
(260 reference statements)
1
96
0
5
Order By: Relevance
“…Despite the emergence of this gender difference during puberty, the trauma-and anxiety-related symptoms are negatively correlated with the endogenous estradiol levels (Angold et al, 1998;Hankin and Abramson, 1999;Lebron-Milad and Milad, 2012). Congruent with an increased vulnerability to affective disorders during periods of low endogenous estradiol such as menopause, postpartum and following oophorectomy (Altshuler et al, 1998;Harsh et al, 2009;Parker et al, 2009;Schmidt and Rubinow, 2009;Schnatz et al, 2010), an impairment in fear extinction, an inhibitory learning process that attenuates anxiety symptoms, has been associated with low endogenous estradiol (Davis, 2011;Milad et al, 2010). Although an estradiol-based approach might be beneficial in the management of anxiety symptoms, its multifaceted effects are a limitation for therapeutic utilization (Hall et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the emergence of this gender difference during puberty, the trauma-and anxiety-related symptoms are negatively correlated with the endogenous estradiol levels (Angold et al, 1998;Hankin and Abramson, 1999;Lebron-Milad and Milad, 2012). Congruent with an increased vulnerability to affective disorders during periods of low endogenous estradiol such as menopause, postpartum and following oophorectomy (Altshuler et al, 1998;Harsh et al, 2009;Parker et al, 2009;Schmidt and Rubinow, 2009;Schnatz et al, 2010), an impairment in fear extinction, an inhibitory learning process that attenuates anxiety symptoms, has been associated with low endogenous estradiol (Davis, 2011;Milad et al, 2010). Although an estradiol-based approach might be beneficial in the management of anxiety symptoms, its multifaceted effects are a limitation for therapeutic utilization (Hall et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In OWD, secretion of noradrenaline was quickly restored after SBE, and exceeded that in healthy women. Estrogen improves the steatolysis action of noradrenaline, and it is considered that the reduced secretion of estrogen together with a decrease of ovarian function, which occurs before menopause in women, leads to obesity (11,21) and depression (27). When we examined urinary E2 before and after one minute of SBE, a surprising increase was revealed.…”
Section: Ham-d Scalementioning
confidence: 99%
“…Therefore, novel approaches for the treatment or prevention of depression in obese individuals are urgently required. It has been reported that in perimenopausal women, age-related changes in ovarian estrogen production may alter the function of the autonomic nervous system and thus predispose them to depression (27). Following initial studies of the association between obesity and autonomic nervous activity, we focused on depression, especially that affecting obese women.…”
mentioning
confidence: 99%
“…Twenty percent of outpatient have menopausal depression 1) . Women in menopausal period have one or more of menopausal symptoms 2) , and primary factor includes depressant episode, vasomotor symptom and pessimism about life 3) , and change of hormone related menopausal depression 4) . According to recent longitudinal cohort studies, the probability of depressed mood in the menopausal transition is approximately 30% to three times greater compared with that of premenopausal period.…”
Section: ⅰ Introductionmentioning
confidence: 99%